Perbandingan Hukum Penegakan Tindak Pidana Perdagangan Orang (Studi Perbandingan Hukum Indonesia dan Amerika Serikat) - Febriana, Dinda Putri; Nuroh; Rizqika Ayu Amalia; Ismi Korifah; Loso; Ganis Vitayanty Noor (Cahaya Ilmu Bangsa, 2025)
Human trafficking is a transnational crime that requires an effective legal approach. Indonesia and the United States of America have different legal systems in addressing human trafficking, particularly in regulation, law enforcement, and victim protection. Indonesia enforces Law No. 21 of 2007 on the Eradication of Human Trafficking, yet faces challenges in implementation due to weak inter-agency coordination and the involvement of corrupt officials. Meanwhile, the United States relies on the Trafficking Victims Protection Act (TVPA) of 2000, which provides a more comprehensive legal framework supported by strong law enforcement mechanisms. Although the United States of America legal system is more effective in investigating and prosecuting traffickers, strict immigration policies often deter victims from seeking help. In contrast, Indonesia struggles with weak law enforcement and inadequate victim protection measures. This study highlights the need for Indonesia to enhance coordination, transparency, and technological utilization in trafficking investigations, while the United States of America should consider revising its immigration policies to be more victim-friendly. Collaboration between both countries in information sharing and investigative strategies is essential to improving anti-trafficking efforts and strengthening victim protection.